1992
DOI: 10.2519/jospt.1992.16.5.229
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of a Hand-Held Dynamometer with Two Populations

Abstract: current positive trend is the integration of people with mental retardation into all as-,pects of our society. Persons with mental retardation are being encouraged to engage in sports, physical fitness, and recreational activities. Integration into society has taken place in all phases of living, including the seeking of medical treatment at local hospitals and sports medicine clinics.Evaluation of strength is an integral component in a rehabilitation o r conditioning program. Although isokinetic dynamometry h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 9 publications
1
29
1
Order By: Relevance
“…As anticipated, this study demonstrates that MMT and an HHD are appropriate for EMG normalization in the quadriceps muscle. Our findings are consistent with previous studies that have examined the concurrent validity of EMG activity and maximal muscle strength of the quadriceps muscle measured by MVIC methods such as MMT, HHD, and SD in healthy young adults, elderly people, and adults with mental retardation 4,[36][37][38] . In EMG study, Lin et al (2008) only compared the EMG activity measured by MMT and a Cybex dynamometer during maximal isometric quadriceps contraction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As anticipated, this study demonstrates that MMT and an HHD are appropriate for EMG normalization in the quadriceps muscle. Our findings are consistent with previous studies that have examined the concurrent validity of EMG activity and maximal muscle strength of the quadriceps muscle measured by MVIC methods such as MMT, HHD, and SD in healthy young adults, elderly people, and adults with mental retardation 4,[36][37][38] . In EMG study, Lin et al (2008) only compared the EMG activity measured by MMT and a Cybex dynamometer during maximal isometric quadriceps contraction.…”
Section: Discussionsupporting
confidence: 92%
“…The differences in the mean EMG amplitude ratio and the median frequency between MMT and Cybex testing were not statistically significant 4) . In terms of quadriceps strength, Surburg et al (1992) first examined the correlation between an HHD and Cybex II dynamometer in terms of isometric quadriceps strength using a stabilization technique with straps in adults with mental retardation (intelligence range based upon the Stanford-Binet Intelligence Test: 36 to 69) and found that significant Pearson coefficients (r) ranged from 0.72 to 0.76 38) . Reed et al (1993) and Martin et al (2006) reported that the correlation between HHD and SD measurements for elderly adults was fair (r = 0.74) and high (r = 0.91), respectively 36,37) .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the correlations obtained in this study were similar to those reported by previous studies using both procedures in isometric mode. 20,23 Second, we also used dierent positions to evaluate certain muscle groups. For example, shoulder abductors and adductors were assessed in a 458 sitting position with Cybex while gravity was eliminated with the myometer.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate trunk muscle strength and endurance increase the risks of lower back pain, falls and dependence in daily living activities. Muscle strength tests provide very important information to help guide therapeutic interventions for patients with neurological and orthopedic disorders in the clinical setting [1][2][3][4][5][6][7][8] . Two tests are commonly used to clinically assess and monitor trunk flexor strength.…”
Section: Introductionmentioning
confidence: 99%